A Results-Oriented Approach for the Animal Welfare Measure of the European Union’s Rural Development Programme - Angela Bergschmidt; Solveig March; Kathrin Wagner; Jan Brinkmann (Animals, 2021)
Farm animal welfare is a major concern to the European Union’s citizens, addressed in the Rural Development Programmes by a specific animal welfare support measure. Previous evaluation results reveal that the implemented action-oriented measures fail when it comes to improving animal health, an important dimension of animal welfare. Results-oriented measures could compensate for this deficiency, but little is known about their design. In order to improve the effectiveness of current animal welfare measures for dairy cows, we analysed the elements of such a measure in an interdisciplinary, application-oriented research project involving agricultural economists and livestock scientists. We have used a mixed methods approach including a written Delphi survey, group-discussions and on-farm data-collection to select suitable indicators, develop an approach for the identification of threshold values and to design a support measure. Results suggest that, in animal welfare support measures, action- as well as results-oriented elements are necessary to address all dimensions of animal welfare.